Spectral Characterization of Stem Cell-Derived Myelination within the Injured Adult PNS Using the Solvatochromic Dye Nile Red - Joey Grochmal (Cells, 2020)
Background: Myelin is an essential component of the peripheral and central nervous system, enabling fast axonal conduction and supporting axonal integrity; limited tools exist for analysis of myelin composition in-vivo. Objective: To demonstrate that the photophysical properties of myelin-incorporated solvatochromic dyes can be exploited to probe the biochemical composition of living peripheral nerve myelin at high spatial resolution. Methods: Using the myelin-incorporated fluorescent dye Nile Red we sequentially analyzed the spectral characteristics of remyelinating myelin membranes both in-vitro and in-vivo, including in living rats. Results: We demonstrated a consistent bi-phasic evolution of emission spectra during early remyelination, and visually report the reliable biochemical flux of myelin membrane composition in-vitro and in-vivo. Conclusions: Solvatochromic spectroscopy enables the analysis of myelin membrane maturity during remyelination, and can be performed in-vivo. As the formation of myelin during early-to-late remyelination likely incorporates fluctuating fractions of lipophilic components and changes in lateral membrane mobility, we propose that our spectrochemical data reflects the observation of these biochemical processes.